2013
DOI: 10.4028/www.scientific.net/kem.554-557.2266
|View full text |Cite
|
Sign up to set email alerts
|

Earing Prediction in Drawing and Ironing Processes Using an Advanced Yield Criterion

Abstract: This work aims to contribute to the understanding of the role/influence of advanced yield criteria on the earing profile prediction after drawing and ironing, for a cylindrical cup benchmark proposed at the NUMISHEET 2011 conference [1]. Two typical materials used for can-making were considered and studied: an AA5042 aluminum alloy and an AKDQ steel. The drawing and ironing operations are performed on a special die which allows drawing and ironing in one single punch stroke in order to simplify the real proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…However, the conditions that guarantee the convexity of CB2001 are unknown. Therefore, following Soare et al [17], the minimisation process adopted includes testing the convexity of the yield surface for several planes in the stress space [34]. For metal sheets the parameters a 5 , a 6 and b k (k = 6, 7, 8, 9, 11) cannot be evaluated, thus the corresponding isotropy condition values are commonly adopted, i.e.…”
Section: Cazacu and Barlat 2001 (Cb2001)mentioning
confidence: 99%
“…However, the conditions that guarantee the convexity of CB2001 are unknown. Therefore, following Soare et al [17], the minimisation process adopted includes testing the convexity of the yield surface for several planes in the stress space [34]. For metal sheets the parameters a 5 , a 6 and b k (k = 6, 7, 8, 9, 11) cannot be evaluated, thus the corresponding isotropy condition values are commonly adopted, i.e.…”
Section: Cazacu and Barlat 2001 (Cb2001)mentioning
confidence: 99%
“…Chung et al, 1997;Dick et al, 2007 ). Barros et al (2013) reported the accurate prediction of the earing during cup drawing depends not only on the correct modeling of the materials mechanical behavior but also on the accuracy of the global process modeling including the blank holder, the yield criterion selected, the work hardening law and the strategy used to identify the materials parameters. Neto et al (2016) studied the influence of elastic deformation of the tooling during cup drawing and concluded the accuracy of the sheet metal forming simulation can be improved considering the elastic deformation of the forming tools in the numerical model.…”
Section: Materials Plasticity -Earing Predictionmentioning
confidence: 99%
“…Rolling texture components favor earing principally at 45 • /135 • with respect to the RD [4,5]. With regards to earing, a low ear ratio can be achieved through an optimal combination of crystals with an orientation that results in both 45 • /135 • and 0 • /90 • ears [6][7][8][9]. The crystallographic components which are formed during recrystallization depend on the stacking fault energy (SFE), the previous deformation state, the annealing temperature as well as the precipitation state.…”
Section: Introductionmentioning
confidence: 99%